Analysis Of Elpiji Gas User Consumer Perception - Aprian Sadlin; Sri Ernawati (Jambura Science of Management, 2020)
This study aims to determine the perception of consumers of Liquefied Petroleum Gas (LPG) gas in Bima City. This type of research is quantitative descriptive. In this study the data used are primary data obtained from consumer LPG user questionnaires in the Bima City. Data were analyzed using univariable one-sample t-test analysis. The instrument was obtained from a questionnaire (questionnaire) that would be distributed and answered by LPG consumer users in the form of Likert scale questions. The population in this study is LPG consumer consumers in the City of Bima. The sample used is calculated using the formula Unknown Populations and the number of samples obtained is 96 consumers. As for the sampling technique using the accidental sampling method. After processing data using several statistical tools such as average values and descriptive analysis, the results of this study are the perceptions of LPG users who on average give good answers. LPG users state that the use of gas is more profitable than kerosene, in terms of cost being more economical, the cooking process is also faster and cleaner and there is no compulsion and receiving gas as a substitute for kerosene.